Perché gli studenti universitari decidono di abbandonare gli studi? - Testa, Italo; Galano, Silvia; Tarallo, Oreste (Chimica nella Scuola, 2024)
In this paper, we investigated the self-assessment ability of first-year students in the Biology and Engineering degree programs engaged in chemistry and physics teaching, respectively, courses that students usually encounter in the first semester of their first year. Specifically, we investigated the correlations between students’ self-assessment ability and the likelihood that they would pass the final exam for the course. Our study shows that students who are more likely to pass the exam are the most calibrated while students who are less likely to pass the exam turn out to be typically over-confident. It also turns out that boys are on average more over-confident than girls.